Vacancy Duration and Wages - Bassier, Ihsaan; Manning, Alan; Petrongolo, Barbara (The Review of Economics and Statistics, 2025)
Abstract We estimate the elasticity of vacancy duration with respect to posted wages, using data from the near-universe of online job adverts in the United Kingdom. Our research design leverages firm-level wage policies that are plausibly exogenous to hiring difficulties on specific job vacancies, and controls for job and marketlevel fixed-effects. Wage policies are defined based on external information on pay settlements, or on sharp, internally-defined, firm-level changes. In our preferred specifications, we estimate duration elasticities in the range −3 to −5, which are substantially larger than the few existing estimates.